Electrocatalytic water oxidation by a molecular cobalt complex through a high valent cobalt oxo intermediate. Issue 79 (12th September 2016) - Das, Debasree; Pattanayak, Santanu; Singh, Kundan K.; Garai, Bikash; Sen Gupta, Sayam
Abstract : Biuret-modified tetraamidomacrocyclic cobalt complex [Co III -bTAML] − is shown to catalyze electrochemical water oxidation at basic pH leading to the formation of O2 . Abstract : Biuret-modified tetraamidomacrocyclic cobalt complex [Co III -bTAML] − is shown to catalyze electrochemical water oxidation at basic pH leading to the formation of O2 . Electrochemical and spectroscopic studies indicate a high valent cobalt oxo intermediate isoelectronic to Co V (O) as the active oxidant. The kinetic isotope effect of 8.63 indicates an atom proton transfer mechanism.